“Influencia de cuatro dosis de gallinaza de postura en el rendimiento de grano seco frijol trepador (phaseolus vulgaris) variedad huasca poroto huallaguino empleando el sistema de espaldera en el distrito de Lamas” - Piña Alva, Miguel Antonio (2014)
This research paper entitled "lnfluence of four doses of manure posture in the dry grain yield of climbing bean ( Phaseolus vulgaris) variety Huasca Poroto Huallaga using the trellis system in the district of Lamas " was carried out in arder to evaluate the effect of four doses of manure posture oxide on the performance of dry bean climbing beans (Phaseo/us vulgaris) variety Huasca Poroto Huallaga under the trellis system in the district of Lamas and performing economic analysis of treatments Statistical design for randomized blocks (RCBD) with three and four repeat treatments was used. The results indicate me that with the application of 30 t ha-1 (T3) of manure the highest mean yield, seed weight, number of seeds/pod and number of pods per plant with 22 723,40 kg. ha-1 , were obtained, 0.47 g, 8.3 seed pods per plant and 177. 7 respectively, statistically outperforming the averages of the other treatments, followed by T2 (20 t ha-1), T4 (40 t.ha-1), T1 (10 t.ha-1 ) and TO (control). The T3 (30 t.ha -1 ) treatment had the highest value of B/C to 1.45 anda net profit of S l. 33 605.92 nuevos soles, followed by T2 (20 t ha -1 ) and T4 (40 t ha-1 ) who obtained values of B/C of 0,53 and O, 19 with net profit of S /.11 930.78 and S/. 4 587.88 soles, respectively. The TO (Control) and T1 (1 O Uha-1 ) treatments were negativa B I C values -0.15 and -0.05 respectively. Keywords: lnfluence, dosage, manure, yield, bean trellis, analysis, economic, seed pod weight.